2023
DOI: 10.2337/dc22-1971
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Advanced Hybrid Closed Loop on Youth With High-Risk Type 1 Diabetes Using Multiple Daily Injections

Abstract: OBJECTIVE To evaluate glycemic outcomes in youth (aged 13–25 years) with type 1 diabetes and high-risk glycemic control (HbA1c ≥8.5% [69 mmol/mol]) on multiple daily injection (MDI) therapy after transitioning to advanced hybrid closed loop (AHCL) therapy. RESEARCH DESIGN AND METHODS This prospective, 3-month, single-arm, dual-center study enrolled 20 participants, and all completed the study. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 19 publications
2
5
0
Order By: Relevance
“…The findings of the present case series align with previous studies using other advanced automated insulin delivery systems ( 5 8 ). This consistency of findings underscores the robustness of the AHCL algorithm and supports the application of closed-loop systems across a broad range of individuals with T1D.…”
Section: Discussionsupporting
confidence: 91%
“…The findings of the present case series align with previous studies using other advanced automated insulin delivery systems ( 5 8 ). This consistency of findings underscores the robustness of the AHCL algorithm and supports the application of closed-loop systems across a broad range of individuals with T1D.…”
Section: Discussionsupporting
confidence: 91%
“…Uncontrolled trials confirmed these data. TBR was shown to always remain at target, with a TIR improvement of approximately 10% in people living with diabetes who were on the PLGM system before using AHCL [ 20 , 21 , 26 ], and an even larger improvement of approximately 35–40% in those using MDI therapy before AHCL [ 24 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Similar to the MiniMed™ 670G system, the 780G system proved to be safe in regard to the prevention of severe hypoglycaemia. No episodes were reported under any study condition, including an experimental setting with a late meal bolus [ 20 ] or flex vs fixed carbohydrate counting [ 27 ], a randomized clinical trial in a free-living setting [ 19 ], a single-arm study with a home setting [ 21 , 24 , 25 , 31 , 34 , 36 ], prolonged fasting due to Ramadan [ 28 ], and even when tested in preschool children [ 26 ]. The study by Tornese et al [ 52 ], which included 12 preschool children and was published after the literature search for this review, confirmed that the MiniMed 780G™ system may be safe and effective even in children < 7 years of age and with a total daily dose < 8 IU.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations